VD_FINDINFO ML / 2014 / 272 vom 9. Dezember 2014 - VD Tribunal cantonal (2014)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, CESSION DE CRÉANCECO, COMPENSATION DE CRÉANCES | 164 al. 1 CO, 80 LP, 81 al. 1 LP